Mandibulectomy in feline with bacterial fibrosing osteomyelitis - Sampaio, Keytyanne de Oliveira; Silva, Jéssica Mara da Costa; Oliveira, Alexandre Tavares Camelo; da Silva, Ellen Cordeiro Bento; Nunes-Pinheiro, Diana Célia Sousa; Sousa-Filho, Reginaldo Pereira (Acta Scientiae Veterinariae, 2021)
Background: Fibrosing osteomyelitis is a chronic inflammatory process caused by infectious agents that lead to the destruction and replacement of bone tissue by fibroblasts. The diagnosis is based especially on histopathological and bacterial culture. In cases where extensive and irreversible injuries are observed, surgical treatment may be indicated. The objective of this work is to report the clinical, radiographic, histopathological, and microbiological aspects of a cat presenting fibrosing osteomyelitis. Case: A 10-year-old male feline, no defined breed, weighing 3.9 kg was referred to one Private Veterinary Clinic of Fortaleza, CE, Brazil with a history of left mandibular enlargement, presenting dysphagia, sialorrhea, an increase in firm consistency along of the left mandibular body, temporomandibular arthralgia and decreased joint motion range. On cranium radiograph, signs of proliferative osteopathy of irregular contours were observed in the branch and body of the left mandible and extending to the rostral region of the right mandible, suggesting a neoplastic process. After anesthesia, for better assessment of the oral cavity, a sample was collected by incisional biopsy, however, the histopathological result was nonspecific. In view of the inconclusive condition, it was decided to perform left hemimandibulectomy combined with right partial mandibulectomy. Tissue samples were obtained and sent for microbiological and histopathological analyses. The last test revealed an inflammatory reaction consisting of neutrophils and plasma cells, associated with a large amount of fibrous connective tissue, multifocal bacterial aggregates, necrosis and bone resorption. Based on the findings, the diagnosis of chronic bacterial osteomyelitis was concluded. The microbiological culture demonstrated the growth of the bacterium Pseudomonas aeruginosa, with sensitivity to cefovecin, which was administered to the treatment in doses of 8 mg/kg/SC, every 15 days, for 60 days. After 10 days of the surgery, the patient was able to start the process of swallowing and seizing pasty food. Discussion: Although radiography is a diagnostic method of choice to assess the extent of bone involvement, it hardly allows the distinction between neoplastic processes and osteomyelitis. Thus, in addition to the cranium radiographic examination, that revealed signs of proliferative osteopathy with irregular contours in branch and body topography of the left mandible were required biopsy and bacterial culture. After mandibulectomy, difficulty in retracting the tongue and anorexia were observed in the first days. Despite that, from the 12th day on, there was an improvement in food seizure, with the return to voluntary feeding. Mandibulectomy is indicated in cases where extensive and irreversible lesions are observed, although excision of the caudal mandible to the third or fourth premolar tooth is not recommended, because it compromises the sublingual musculature, with fall of the tongue and loss of function apprehension. In the present case, the caudal portion of the right mandibular branch was maintained, which facilitated the return of spontaneous feeding. The tissue removed was necessary to perform a microbiological culture with antibiogram, essential to determine the possible etiologic agent and choosing antimicrobial drugs. For the treatment of P. aeruginosa infection, cefovecin was prescribed due to the dosage and route of administration that collaborate with the mandibular surgery, once that the oral treatment is more difficult. Post-surgical complications related to mandibular resection, such as anorexia and difficulty in grasping food, are common. However, in the present case, the patient had an adequate reestablish after 15 days. Therefore, hemimandibulectomy is effective in treating fibrosing osteomyelitis, with maintenance of the patient's ingestive function.